2021
DOI: 10.3390/jcdd8020022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selected miRNAs as Diagnostic and Prognostic Biomarkers in Cardiovascular Diseases, Including Coronary Artery Disease, Myocardial Infarction and Atherosclerosis

Abstract: Cardiovascular diseases are the leading cause of death worldwide in different cohorts. It is well known that miRNAs have a crucial role in regulating the development of cardiovascular physiology, thus impacting the pathophysiology of heart diseases. MiRNAs also have been reported to be associated with cardiac reactions, leading to myocardial infarction (MCI) and ultimately heart failure (HF). To prevent these heart diseases, proper and timely diagnosis of cardiac dysfunction is pivotal. Though there are many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 118 publications
1
23
0
Order By: Relevance
“…Importantly, abundant and stable miRNAs can be detected in plasma, and their expression is frequently dysregulated in diseases [ 10 ]. Multiple circulation miRNAs have been reported as an ideal cluster of blood-based biomarkers for many diseases such as cancer and cardiac diseases [ 11 , 12 ]. However, the mechanisms underlying the miRNA interaction with the inflammation in HF have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, abundant and stable miRNAs can be detected in plasma, and their expression is frequently dysregulated in diseases [ 10 ]. Multiple circulation miRNAs have been reported as an ideal cluster of blood-based biomarkers for many diseases such as cancer and cardiac diseases [ 11 , 12 ]. However, the mechanisms underlying the miRNA interaction with the inflammation in HF have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hsa-miR-933, RELB, and CCL21 may be correlated with HF and neurological disorders. Previous studies have found that miRNAs in circulating blood alone also have the potential to predict dementia and HF [38][39][40]. This is because the information in circulating blood miRNAs is suggestive of essential organismal conditions such as ischemic, cardiomyopathy, diabetes, and valvular [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death in the world, including cardiac failure, coronary heart disease, myocardial infarction and atherosclerosis ( Mir et al, 2021 ). Atherosclerosis is one of the most common causes of cardiovascular disease ( Poznyak et al, 2021 ).…”
Section: Phytochemical-mediated Mitophagy In Metabolic Disordersmentioning
confidence: 99%